2008
DOI: 10.1007/s10562-008-9420-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cocatalyst and Calcination Temperature on Photocatalytic Hydrogen Evolution Over BaTi4O9 Powder Synthesized by the Polymerized Complex Method

Abstract: BaTi 4 O 9 powders with improved crystal perfection and relatively large surface area were synthesized by the polymerized complex (PC) method calcined at reduced temperatures (700-1,000°C) relative to the solidstate reaction (SSR) method. BaTi 4 O 9 with a unique pentagonal-prism tunnel structure, combined with different cocatalysts (Pt, Ru, Ni, Cu, Co) as promoters, was investigated towards photocatalytic reactions for H 2 evolution from pure water and aqueous ethanol solution. Pt/BaTi 4 O 9 achieved the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…To resolve this issue and enhance the photocatalytic activity of the photocatalyst, various approaches have been employed, including doping the semiconductors with other impurities [16] and optimization of reaction conditions by setting the calcination temperature [17] in order to improve the crystallinity of the material. However, the effects of the calcination temperature on the morphology and photocatalytic activity of La-NaTaO 3 have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…To resolve this issue and enhance the photocatalytic activity of the photocatalyst, various approaches have been employed, including doping the semiconductors with other impurities [16] and optimization of reaction conditions by setting the calcination temperature [17] in order to improve the crystallinity of the material. However, the effects of the calcination temperature on the morphology and photocatalytic activity of La-NaTaO 3 have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a variety of metal oxides with tunnel structure have been found to be active for H 2 production under ultraviolet-light illumination [2][3][4]. Among these oxides, the compound BaTi 4 O 9 with a pentagonal prism tunnel structure has received considerable attention as a new host catalytic material in combination with RuO 2 for stoichiometrically complete photodecomposition of water [5][6][7]. Inoue et al have suggested that the tunnel structure of the BaTi 4 O 9 material has an important effect on the excellent photocatalytic activities since it brings about a significantly large distortion of TiO 6 octahedra, which possibly leads to efficient production of photo-excited charges and prevents RuO 2 particles from aggregating and growing into large particles [3].…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out by Ma et al [156], a lot of papers make claims about "water splitting" while using a so-called hole scavenger [157]; but since no oxygen is evolved in this case, it is more proper to term these reactions as photoreforming or partial water splitting [156]. Despite its attractiveness, this reaction is more difficult than PR, both from a thermodynamic and kinetic point of view, leading to lower hydrogen productivity [158].…”
Section: Proposed Reaction Pathwaymentioning
confidence: 99%
“…Moreover, few comparisons among these non-noble metal co-catalysts exist. Fujita et al reported an increased reactivity, in order, CoO x < NiO < CuO on TiO 2 [226], while Sun et al observed an improved hydrogen evolution, in order, RuO x < NiO < CuO < CoO x < Pt on a barium titanate [158], suggesting that interactions between the co-catalyst and the main semiconductor play a crucial role too. Alloying has been proved to boost the catalytic activity [227][228][229], probably due to synergistic effects among the two components as suggested by Jung et al [230]; unfortunately, these reported alloys contain at least one noble metal, increasing the cost of the catalyst.…”
Section: Catalyst Formulationmentioning
confidence: 99%